Electricity - Jenner, Elizabeth; Chomet Heloise; Brave the Woods (London : Ladybird Books, 2021)
Discover the scientists and the experiments that have helped us create different types of electricity. Explore how electric currents appear in nature, from static to lightning bolts, and how these natural marvels inspired scientists to conduct experiments. In this book, you can see how we create electricity and the many ways it is used every day.
"A Ladybird Book".
Keywords: Electricity -- Juvenile literature